Write the equation that satisfies the parameters: three times the difference of a number and 10 equals the sum of 25 and that same number. (1 point) 3x + 10 = 25 - x; 3x - 10 = 25 + x; 3(x + 10) = 25 - x; 3(x - 10) = 25 + x

1 answer

The problem states that three times the difference of a number and 10 equals the sum of 25 and that same number. Let's denote the unknown number as \( x \).

  1. The difference of the number and 10 can be written as \( x - 10 \).
  2. Three times this difference is \( 3(x - 10) \).
  3. The sum of 25 and that same number is \( 25 + x \).

Putting it all together, we set up the equation:

\[ 3(x - 10) = 25 + x \]

So, the correct equation is:

\[ \boxed{3(x - 10) = 25 + x} \]